Knowledge and commitment : a problem-oriented approach to literary studies - Fokkema, Douwe Wessel, 1931- (Utrecht publications in general and comparative literature, 2000)
The authors present a new perspective on a wide range of issues in the study of literature and culture. Some of the topics discussed, such as interpretation, canon formation, and literary historiography, belong to the traditional domain of literary studies. Others -- cultural identity, convention, systems theory, and empirical methods -- originate in the social sciences and are now being integrated into the humanities. By referring to the work of authors as widely apart as Hayden White, Edward Said, Fredric Jameson, Michel Foucault, Jacques Derrida, Reinhart Koselleck, Pierre Bourdieu, Niklas Lu.